Representatives of American and Uzbek Literature in 19th and 20th Century (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article provides overview about the representatives of Uzbek and American literature in 19th and 20th century. Particularly, the works of well-known authors and poets were significant both then and now. Despite their struggles, they left behind their masterwork for future generations.